Customer satisfaction towards counter service at Bank Pertanian Malaysia / Zaleha Hasbullah - Hasbullah, Zaleha (2006)
This report is about ‘Customer Satisfaction towards Counter Service at Bank Pertanian Malaysia’. The case study is in Headquarter of Bank Pertanian Malaysia. The objective of the study is to determine the level of customer satisfaction and to identify the factors that affect customer satisfaction at counter service of Bank Pertanian Malaysia. Researcher used questionnaire in order to obtain data. The questionnaires are based on the elements of service quality, elements of service features and customer complaint handling. Likert scales were used in that questionnaire. In this study, the researcher analyzed and interpreted data from the questionnaires and the results was compute through descriptive statistics of frequency and means procedure. There where 100 numbers of respondents were involved in this study. Based on the findings, Bank Pertanian Malaysia can improve the service quality, service features and customer complaint handling in order to increase the customer satisfactions toward counter service of Bank Pertanian Malaysia.